Territorios Ecoeficientes: Hub económico y empresarial para el Caribe (2017)
In a globalized world where countries are competing to be more productive and competitive, there is a need to adopt high-level national strategies in innovation and creativity, which allow the territories to be de-territorialised by increasing growth and development, the capacity for services provided and grouping Small economic links, thus forming major production chains of global relevance. In reference to this, environmental, administrative, social and economic policies favoring the present and future potentials of a territory have been chosen. In the case of the Colombian Caribbean, as an intervention area, the logistical and service potential arising from its strategic Location, to interact with international markets, making it a motor for national development, which benefits its population by providing better employment opportunities than tourism and encouraging investment in the region in infrastructure and basic services.